Dental Findings in Patients With Non-surgical Hypoparathyroidism and Pseudohypoparathyroidism: A Systematic Review - Hejlesen, Jane; Underbjerg, Line; Gjørup, Hans; Bloch-Zupan, Agnes; Sikjaer, Tanja; Rejnmark, Lars; Haubek, Dorte (Frontiers in Physiology, 2018)
Background: Dental aberrations have been mentioned in relation to non-surgical hypoparathyroidism (Ns-HypoPT) and pseudohypoparathyroidism (PHP). However, a systematic review of dental characteristics have not been performed. The present systematic review describes the dental findings in patients with Ns-HypoPT and PHP. Methods: Studies on Ns-HypoPT and PHP reporting dental features were eligible. A systematic literature search was conducted using four bibliographic databases (Web of Science, Scopus, Pubmed and Embase) and was limited to studies written in English. Reviews, meta-analyses and letters were excluded. Both the research and reporting of results were based on PRISMA (preferred Reporting Items for Systematic Reviews and Meta-Analysis) guidelines. Results: Of 88 studies included, nine were cross-sectional, one was a prospective cohort study, 26 were case series, and 52 were case reports. The most frequently reported findings in patients with Ns-HypoPT were enamel opacities, enamel hypoplasia, hypodontia, and eruption disturbances. In patients with PHP, enamel hypoplasia, eruption disturbance, and deviation of the root morphology were the most frequently reported findings. Conclusion: An association between enamel hypoplasia and Ns-HypoPT and PHP is likely. The results should, however, be interpreted cautiously due to the limited number of high-quality studies. The present review confirms the need of further well-designed studies, such as large-scale studies, e.g., multicenter studies, to conclude on the reported associations between Ns-HypoPT/PHP and enamel hypoplasia.